Time to Shift Focus from Oxidative Stress to Redox Regulation in COPD - Niki L. Reynaert (MDPI AG, 2022)
Chronic obstructive pulmonary disease (COPD) is a non-communicable chronic disease that is top-ranking with respect to mortality and morbidity rates, posing an enormous burden on patients, caregivers and societies at large [...]